Program Pelatihan Coping Self-Efficacy untuk Meningkatkan Self-Esteem Kelompok Basket Putri Selama Pandemi - Mahardika, Dimas; Kandoko, Isabella Vannessa Pranata; Lithioni, Grace Veronica; Meliana, Yenny; Lukika, Olivia; Prayudi, Satrio Dhiaputra; Tondok, Marselius Sampe (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
The Covid-19 pandemic can have a negative impact on the psychological condition of the basketball athlete community from this service activity. The purpose of the service program in the form of psychoeducation to the basketball athlete community is to increase self-esteem and coping self-efficacy. Coping self-efficacy describes a person's ability to perform certain behaviors successfully with the expected results. Self-esteem is a global evaluation of an individual's thoughts and feelings, and evaluations can be positive or negative. The partner groups in this training are four students who are members of the women's basketball group in Samarinda, with an age range of 15-17 years. The training materials are tailored to the needs of the partner community which is explored through needs analysis. The training is carried out online via Zoom in small groups of 4 people. Measurement of the process and results of service activities is carried out through questionnaires, observations, and online interviews. The results of the service showed an increase in self-esteem scores and coping self-efficacy in the partner group. From this training, service partners gain a new and more positive understanding of coping self-efficacy, self-esteem, and its aspects. Partner groups are able to apply the material that has been given in real life as basketball athletes.